Caracterização morfogênica e estrutural de trevo alexandrino submetido a diferentes intervalos e alturas de corte em consorcio com azevém anual. - Conto, Leandro de (2010)
A field experiment was carried out in 2009 at Embrapa Clima Temperado Experiment Station, in Capão do Leão, Rio Grande do Sul State, Brazil, to evaluate the effect of different heights and cutting intervals on morphogenetic and structural characteristics of Berseem Clover x Annual Ryegrass association, as well as forage dry matter yield. Treatments consisted of two residual cutting heights (A1= 5 cm and A2= 10 cm) and harvesting intervals based in thermal sums (GD): (IC= 350 GD; IC2= 450 GD and IC3= 550 GD). A complete randomized block design was used with four replications. In each plot three representative ryegrass stems and three stems of clover, were marked. In both forages the following variables were evaluated: number of live leaves (NFV), number of dead leaves (NFM), rate of leaf appearance (TSF) and phylochrone, as well as daily growth rate (TCD) and dry matter yield (MS) of leaves and stems (kg MS/ha). For the clover it also were evaluated rate of stems appearance (TSR), number of nodes per plant (NNP) and number of stems per plant (NRP). For ryegrass and clover the TCD and was higher at the 450 GD interval with 25.5 and 14.9 kg MS, respectively. Yield of leaves for the clover was higher in both cutting heights and for ryegrass it was higher at IC1 at 10 cm height. Yield of stems of clover was higher in IC2 and A2 and for ryegrass it was higher in IC1 and A2. The TSF for clover and ryegrass, in the regrowth cutting was of 0.032 and 0.132 leaves/day, respectively. No considerable number of dead leaves in clover was observed for treatments; however for ryegrass the NFM was higher in IC2 with 2.667 leaves. Evaluations made in clover four weeks after regrowth showed the best results for TSF of 0.247 leaves/day; phylocrone of 4.211 °C/day/leaf in IC2 an TSR of 0.136 stems/day. For NNP and NRP the highest values were in IC3 with 31.815 and 4.390, respectively. The NFV was higher in IC2 and IC3 with 8.709 and 9.168 leaves, respectively, without significant statistical difference. Cuttings made at intervals of 450 GD showed to be the ideal for this type of mixture, where the best forage characteristics were observed, as well as favoring both forage species, mainly the legume which contributes to the pasture quality. Morphogenetic and structural characteristics are not affected by changing from 5 cm to 10 cm the residual cutting height. 12